Nanopatterning protein antigens to refocus the immune response. Issue 32 (6th August 2019) - Arsiwala, Ammar; Varner, Chad; McCaffery, Jessica N.; Kell, Andrew; Pendyala, Geetanjali; Castro, Ana; Hariharan, Vivek; Moreno, Alberto; Kane, Ravi S.
Abstract : Nanopatterning is used to shield targeted protein epitopes, enabling the immune response to be refocused to conserved regions on the protein. Abstract : Vaccines for many important diseases remain elusive, and those for others need to be updated frequently. Vaccine efficacy has been hindered by existing sequence diversity in proteins and by newly-acquired mutations that enable escape from vaccine-induced immune responses. To address these limitations, we developed an approach for nanopatterning protein antigens that combines the site-specific incorporation of non-canonical amino acids with chemical modification to focus the immune response on conserved protein regions. We demonstrated the approach using green fluorescent protein (GFP) as a model antigen and with a promising malaria vaccine candidate, Merozoite surface protein 119 (MSP119 ). Immunization of mice with nanopatterned MSP119 elicited antibodies that recognized MSP119 from heterologous strains, differing in sequence at as many as 21 of 96 residues. Nanopatterning should enable the elicitation of broadly protective antibodies against a wide range of pathogens and toxins.